In silico Screening of Natural Phytocompounds Towards Identification of Potential Lead Compounds to Treat COVID-19 - Sankar, Muthumanickam; Ramachandran, Balajee; Pandi, Boomi; Mutharasappan, Nachiappan; Ramasamy, Vidhyavathi; Prabu, Poorani Gurumallesh; Shanmugaraj, Gowrishankar; Wang, Yao; Muniyandai, Brintha; Rathinasamy, Subaskumar; Chandrasekaran, Balakumar; Bayan, Mohammad F.; et al. (Frontiers in Molecular Biosciences, 2021)
The COVID-19 is one of the families of Coronavirus that can easily assail to humans. As of now, 10 million people are infected and above 2 million people died from COVID-19 globally. Over the past one year, several researchers have been made essential advances in discovering potential drugs. Till now, no efficient drugs are available in the market. The present study aims to identify the potent phytocompounds from different medicinal plants (Zingiberoffinale, Cuminum cyminum, PiperNigrum, Curcuma Longa and Allium Sativum). Totally 227 phytocompounds are identified and it was screened against S-ACE2 and Mpro through the Structure-Based Virtual Screening approaches. Based on the binding affinity score, 30 active phytocompounds are selected. The binding affinity for Beta-sitosterol and Beta-Elemene against S-ACE2 has shown -12.0 and -10.9 kcal/mol respectively. Meanwhile, the binding affinity for the Beta-sitosterol and Beta chlorogenin against Mpro is found to be -9.7 and -8.4 kcal/mol respectively. Further, the selected compounds are proceed with Molecular Dynamics Simulation, Prime MM-GBSA and ADME/T properties to understand the stability, interaction, conformational changes, Binding Free Energy and pharmaceutical relevant parameters. Moreover, the hotspot residues such as Lys31 and Lys353 for S-ACE2 and catalytic dyad His41 and Cys145 for Mpro are actively involved in the inhibition of viral entry. From the analyses, we anticipate that this work could be valuable to ongoing novel drug discovery with potential treatment for COVID-19.